PERBEDAAN TINGKAT PENGETAHUAN ANTARA METODE CERAMAH DAN PENGGUNAAN VIDEO ANIMASI DALAM PENYULUHAN KESEHATAN HIV/AIDS PADA SISWA - Iskandar Iskandar; Nursa’adah Nursa’adah; Fani Fani; Riyan Mulfianda; Putri Dini Meutia (Jurnal Dedikasi Pendidikan, 2022)
Aceh Provincial Health Office in 2019, new HIV cases in Aceh have reached 49 people and new AIDS cases have reached 79 people, while the cumulative cases of HIV/IADS reached 600 people with a mortality rate of 309 or 51.5% of the number of people living with HIV/AIDS. One of the factors that influence the occurrence of HIV/AIDS among adolescents is the lack of accurate information. Education about how AIDS is transmitted and prevented is the main weapon against HIV/AIDS, because no treatment or vaccine can prevent the spread of HIV/AIDS. One form of education for adolescents is through health counseling where the counseling that can be given is counseling on reproductive health, especially HIV/AIDS. The purpose of this study was to determine the difference in the level of knowledge between the lecture method and the use of animated videos in HIV/AIDS health counseling to students at MAN 4 Jeunieb District, Bireuen Regency in 2021. This type of research is quasi-experimental, using a two-group pretest posttest design, the research was carried out on 8 to 9 June 2021. The population in this study was all students of class X, XI and XII Madrasah Aliyah Negeri 4 Jeunib District, Bireuen Regency, with sampling using proportional random sampling technique as many as 82 people who are divided into two groups. The results showed that there was a difference in the level of knowledge between the lecture method and the use of animated videos in HIV/AIDS health education to students with p-value = 0.000. It is hoped that this research can provide significant information for teachers and UKS officers in conducting socialization for students/adolescents about the negative impacts caused by HIV/AIDS in the school environment.